Contextual and Critical Analysis of the á¸¤adith of Khalid bin al-Walid's Troop to Bani Jadhimah - Abeebllahi Obalowu Issah; Adibah Binti Abdul Rahim (International Journal of Islamic Khazanah, 2023)
Khá¾±lid bin al-WalÄ«d -may Allah be pleased with him- is one of the noble companions of the Prophet (pbuh) whose image and dignity are being tarnished, especially by the Shiites and orientalists. He is being accused of savagery towards the Muslims during the battles. Thus, he is alleged to have been a war criminal. So, this paper intends to primarily explore one of the major narratives that have been exploited against this noble companion by presenting a contextual and critical analysis of the Incident of Khá¾±lid bin al-WalÄ«d's troop to BanÄ« JadhÄ«mah. Considering the nature of the research, the qualitative method is adopted by visiting the related á¸¥adÄ«ths and historical sources, together with the Islamic historian's remark. Therefore, analytical and critical approaches are applied to analyze and examine the narrations. The outcome of the investigation reveals that the details of the Incident were not reported in any reliable sources of á¸¥adÄ«th. However, they were only reported in historical sources with unsatisfactory isná¾±d, upon which we can not rely to rebuke such a great companion. Besides, none of the historians among the narrators of the event tried to justify Khá¾±lid's action and defend him or report the event without any remark. In addition, the Incident neither affects Khá¾±lid's companionship nor tarnishes his reputation. Hence the Prophet (pbuh) appointed him to lead several military activities afterwards. Likewise, the great Caliph of the Prophet (pbuh) AbÅ«bakr assigned the leadership position to him during his caliphate.